Distributions of Birkeland Current Density Observed by AMPERE are Heavy‐Tailed or Long‐Tailed. Issue 2 (29th January 2022) - Coxon, John C.; Chisham, Gareth; Freeman, Mervyn P.; Anderson, Brian J.; Fear, Robert C.
Abstract: We analyze probability distributions of Birkeland current densities measured by the Active Magnetosphere and Planetary Electrodynamics Response Experiment. We find that the distributions are leptokurtic rather than normal and they are sometimes heavy‐tailed. We fit q ‐exponential functions to the distributions and use these to estimate where the largest currents are likely to occur. The shape and scale parameters of the fitted q ‐exponential distribution vary with location: The scale parameter maximizes for current densities with the same polarity and in the same location as the average Region 1 current, whereas the shape parameter maximizes for current densities with the same polarity and in the same location as the average Region 2 current. We find that current densities | J | ≥ 0.2 μA m −2 are most likely to occur in the average Region 1 current region, and second most likely to occur in the average Region 2 current region. However, for extreme currents (| J | ≥ 4.0 μA m −2 ), we find that the most likely location is colocated with the average Region 2 current region on the dayside, at a colatitude of 18°−22°. Plain Language Summary: We use data from a telecommunications satellite network and measure currents flowing along the magnetic field lines above Earth's surface. We look at how strongly these currents flow above different parts of Earth's surface and plot a histogram of the strengths for each of those different locations. We then fit a mathematical model to the histograms to see how those histograms vary with location, and we are able to use the model to work out the probability of a current above a certain strength flowing. This is useful both to gain insights into the physics of the system, but also to gain insights into the potential impacts of these currents on infrastructure on Earth's surface. Key Points: Probability distributions of Birkeland current densities are best‐described by q ‐exponential distributions The probability of currents at any threshold is higher in the Northern Hemisphere Extreme currents are most likely on the dayside at a colatitude of 18°‐22° (colocated with R2)